Mycotoxins - Impact and Management Strategies 2019
DOI: 10.5772/intechopen.78784
|View full text |Cite
|
Sign up to set email alerts
|

Aflatoxin Management Strategies in Sub-Saharan Africa

Abstract: Aflatoxins are natural poisons produced by some members of the Aspergillus section Flavi group. Their control is critical in sub-Saharan Africa as in other parts of the world because of the health and economic dangers that aflatoxins cause. Aflatoxin management requires a pipeline approach (from production to consumption) that addresses the pre-disposing factors to aflatoxin contamination. These strategies will involve strategies at the pre-harvest, peri-harvest and post-harvest stages to prevent contamination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 35 publications
0
10
0
1
Order By: Relevance
“…Smallholder farmers are risk averse and often value savings (labour, time, and cost) more than profit, so minimal financial investments with short repayment periods are necessary criteria for interventions (Kohl et al, 2017;Memedovic and Shepherd, 2008). Aflatoxin awareness campaigns supported by agro-climatic risk predictions can be distributed through policy briefs, regional reports, media and social media reports, and through public and private extensions services (Falade, 2018). Increased information access based on model results can allow smallholders to be more strategic with investments while focusing on minimisation of risk.…”
Section: Improved Agricultural Production and Value For Smallholdersmentioning
confidence: 99%
See 3 more Smart Citations
“…Smallholder farmers are risk averse and often value savings (labour, time, and cost) more than profit, so minimal financial investments with short repayment periods are necessary criteria for interventions (Kohl et al, 2017;Memedovic and Shepherd, 2008). Aflatoxin awareness campaigns supported by agro-climatic risk predictions can be distributed through policy briefs, regional reports, media and social media reports, and through public and private extensions services (Falade, 2018). Increased information access based on model results can allow smallholders to be more strategic with investments while focusing on minimisation of risk.…”
Section: Improved Agricultural Production and Value For Smallholdersmentioning
confidence: 99%
“…The Malabo Declaration, adopted by the African Union at the 2014 Comprehensive Africa Agriculture Development Program, aims to 'develop mechanisms that enhance Africa's capacity for knowledge and data generation and management to strengthen evidence based planning and implementation' (African Union Commission, 2014), and predictive aflatoxin risk modelling can help contribute to the development of strategic policy. Countries typically build networks of trading relationships based on regulatory limits (Falade, 2018), and for the proposed interventions to be effective it will be necessary to support the harmonisation of policies and regulations across trading regions (Okoth, 2016). Enforcing regulatory standards in African countries is difficult for food security reasons, and an estimate by Sirma et al (2018) showed that around 9 million Kenyans would be deprived of the majority of their food supply if standards for cereals were fully enforced.…”
Section: Food Safety and Public Healthmentioning
confidence: 99%
See 2 more Smart Citations
“…This low level of awareness may hinder the implementation of various mitigation strategies. These strategies are divided into two; pre-harvest strategies that are aimed at preventing the fungal contamination in the field and the post-harvest strategies that are applied to the harvested products during harvesting, processing, or storage to prevent contamination and reduce or eliminate the mycotoxin contamination [97,98]. Prevention of contamination is the preferable method, and post-harvest mitigation strategies are, therefore, very important.…”
Section: Mycotoxin Mitigation Strategiesmentioning
confidence: 99%